Genetics and Epigenetics of Parathyroid Carcinoma - Marini, Francesca; Giusti, Francesca; Palmini, Gaia; Perigli, Giuliano; Santoro, Roberto; Brandi, Maria Luisa (Frontiers in Endocrinology, 2022)
Parathyroid carcinoma (PC) is an extremely rare malignancy, accounting less than 1% of all parathyroid neoplasms, and an uncommon cause of primary hyperparathyroidism (PHPT), characterized by an excessive secretion of parathyroid hormone (PTH) and severe hypercalcemia. As opposed to parathyroid hyperplasia and adenomas, PC is associated with a poor prognosis, due to a commonly unmanageable hypercalcemia, which accounts for death in the majority of cases, and an overall survival rate of 78-85% and 49-70% at 5 and 10 years after diagnosis, respectively. Surgical removal of tumoral gland(s) is the treatment mainly employed, presenting, however, persistent or recurrent disease in about 50% of patients; no definitively effective therapies for PC are currently available. The comprehension of genetic and epigenetic bases and molecular pathways that characterize parathyroid carcinogenesis is important to distinguish malignant PCs from benign adenomas, and to identify specific targets for novel therapies. Germinal heterozygote inactivating mutations of the CDC73 tumor suppressor gene, with somatic loss of heterozygosity at 1q31.2 locus, account for about 50-75% of familial cases; over 75% of sporadic PCs harbor biallelic somatic inactivation/loss of CDC73. Recurrent mutations of the PRUNE2 gene, a recurrent mutation in the ADCK1 gene, genetic amplification of the CCND1 gene, alterations of the PI3K/AKT/mTOR signaling pathway, and modifications of microRNA expression profile and gene promoter methylation pattern have all been detected in PC. Here, we review the current knowledge on gene mutations and epigenetic changes that have been associated with the development of PC, in both familial and sporadic forms of this malignancy.